Lost scriptures : books that did not make it into the New Testament - Ehrman, Bart D. (Oxford University Press, 2003)
A companion anthology paired with Ehrman's ""Lost Christianities"". This book provides an array of the varied writings of Lost Christianities - those early Christian groups whose understanding of Jesus did not win the day, whose views did not make it into the canon of the New Testament